Hirminūtīk-i Ṣūfiyānah : Dar tafsīr-i Kashf al-asrār-i Maybudī - Maybudī, Rashīd al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Rashīd al-Dīn Maybudī (fl. early 6th/12th century) was a Persian scholar and mystic who is best known for his voluminous commentary on the Qurʾān, the Kashf al-asrār wa-ʿuddat al-abrār . The commentary breaks down into 465 'sessions' ( majlis , here: 'lectures') around a number of verses and their explanation. Each session divides into three 'rounds' ( nawba ): 1. the Arabic text and its Persian translation, 2. a standard commentary, and 3. a mystical appreciation of the deeper levels of the text. While the first two rounds are equally in Arabic and Persian, round three is usually mostly in Persian, indicating that Maybudī wanted to ensure that his words were comprehensible to interested non-academics, notably to mystics. Annabel Keeler's Sufi Hermeneutics: The Qur'an Commentary of Rashīd al-Dīn Maybudī , offered in Persian translation here, analyses Maybudī's work from three angles: mystical hermeneutics, Maybudī's borrowings from the mystic ʿAbdallāh Anṣārī (d. 481/1088), and his mystical interpretation of the Qurʾān on prophets.